Rev. Mr. St. John journal - St. John, Rev. Mr.
Journal (1859 December 22-1860 August 9) kept by St. John on a voyage along the African coast pertaining to the slave trade.
Positive photocopy is also available.
Clergyman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Slave trade; Africa -- Description and travel; Clergy